Additive for lithium-ion secondary battery electrode

JP2025026654AActive Publication Date: 2025-02-21NIPPON DENKO CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2024215839
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-02-09
Filing Date
2024-12-10
Publication Date
2025-02-21
Estimated Expiration
2042-02-07

AI Technical Summary

Benefits of technology

【0013】 本発明によれば、リチウムイオン二次電池電極と電解液の界面反応抵抗が小さくなって電圧降下が小さくなるため、高速充放電時に特に優れた入出力特性を有する、即ち、レート特性に優れたリチウム二次電池電極を製造することができる、リチウムイオン二次電池電極の添加材を提供することが可能になる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025026654000001_ABST
    Figure 2025026654000001_ABST
Patent Text Reader

Abstract

To achieve an additive that can be added to an electrode of a lithium-ion secondary battery to improve its characteristics.SOLUTION: An additive for a lithium-ion secondary battery electrode is a composite oxide having a garnet-type or garnet-like crystal structure containing elements of Li, La, Zr, and O, in which a portion of the element Li is substituted with an element A which is different from the elements and can form Li-site vacancies, has a Li-site vacancy ratio of 40% or more and 80% or less, and has an ionic conductivity of 1×10-5 S / cm or more at room temperature.SELECTED DRAWING: Figure 2
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an additive that can be added to an electrode of a lithium ion secondary battery to improve the characteristics thereof. [Background technology]

[0002] Lithium-ion batteries are used not only as small power sources for portable electronic devices such as personal computers and smartphones, but also as large stationary emergency power sources. In recent years, lithium ion batteries have been developed to have large capacity, high-speed charge / discharge characteristics, good cycle characteristics, and excellent safety for use in electric vehicles, hybrid electric vehicles, and the like.

[0003] Patent Document 1 discloses that a lithium ion battery in which a garnet-type oxide is mixed into the positive electrode material has improved cycle characteristics and thermal stability.

[0004] Garnet-type oxide Li7La3Zr2O containing the elements Li, La, Zr, and O 12 The crystal structure of LLZ (hereinafter referred to as LLZ) mainly consists of cubic and tetragonal crystals. It is known that by replacing a specific element constituting LLZ with another element, the cubic LLZ becomes stable and has high ionic conductivity (ionic conductivity). In Non-Patent Document 1, it is reported that in the crystal structure of LLZ, element Li occupies two types of crystallographic sites, Li1 and Li2 sites, which are located at the tetrahedral 24d site and the distorted octahedral 96h site, respectively, and the occupancy rates of each Li site are Li1 = 0.97 (7) and Li2 = 0.349, with the parentheses indicating the standard deviation. It has also been reported that the conduction path of Li ions in LLZ moves along the Li2 → Li1 → Li2 site via the Li1 site, and a three-dimensional network of Li ion migration paths is formed within the LLZ structure.

[0005] In Non-Patent Document 2, it is said that when Ga is substituted for LLZ, Ga substitutes for a part of the Li1 site of the element Li, and Li+ and Ga 3+ It has been reported that the introduction of Li vacancies due to the difference in charge of the LLZ can form a cubic lattice with high ionic conductivity. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2011-113655 A

[0007] [Non-Patent Document 1] J.Awaka et al.,Chem.Lett.,2011.40.60-62 [Non-Patent Document 2] C.Bernuy-Lopez et al.,Chem.Mater.,2014.26.3610-3617 Summary of the Invention [Problem to be solved by the invention]

[0008] The lithium ion battery described in Patent Document 1 above has excellent high-temperature cycle characteristics and thermal stability of the positive electrode, but its input / output characteristics are insufficient. The inventors' investigations have revealed that the discharge voltage and charge / discharge capacity decrease significantly, particularly when the current value during charge / discharge is increased (during high-rate charge / discharge). Improving the rate characteristics of lithium-ion batteries is desirable because it leads to shorter charging times and discharge characteristics that can handle large loads. Currently, rate characteristics are improved by adjusting the particle size of the positive electrode material and the thickness of the positive electrode coating on the current collector. However, reducing the particle size of the positive electrode material to improve the rate characteristics reduces the packing density, resulting in a decrease in battery capacity. In addition, reducing the thickness of the positive electrode coating on the current collector to improve the rate characteristics also results in a decrease in battery capacity. Therefore, a battery that has excellent rate characteristics even with a normal positive electrode structure is desired.

[0009] The object of the present invention has been made in view of the above problems, and is to provide an additive material for lithium ion secondary battery electrodes, which, when added to the electrodes of a lithium ion secondary battery, enables the manufacture of a lithium ion secondary battery having excellent input / output characteristics in which the discharge voltage and charge / discharge capacity are not likely to decrease even when the battery is charged and discharged at high speed, that is, excellent rate characteristics. [Means for solving the problem]

[0010] In order to solve the above problems, the present inventors have developed a composite oxide having a garnet-type or garnet-type-like crystal structure containing the elements Li, La, Zr, and O, in which some of the elements are replaced with an element A different from the elements, the oxide has a Li site vacancy ratio of 40% to 80%, and has an ionic conductivity of 1×10 at room temperature. -5 The present inventors have found that when a composite oxide having a specific conductivity of 0.1 S / cm or more is added to an electrode of a lithium ion secondary battery, the battery has excellent input / output characteristics during high-speed charging / discharging, i.e., the rate characteristics are significantly improved, and have completed the present invention.

[0011] The gist of the present invention is as follows.

[0012] (1) A composite oxide having a garnet-type or garnet-type-like crystal structure containing the elements Li, La, Zr, and O, in which a part of the element Li is replaced by an element A that is different from the elements Li and can form Li-site vacancies, has a Li-site vacancy ratio of 40% to 80%, and has an ionic conductivity of 1×10 at room temperature. -5 An additive for a lithium ion secondary battery electrode, characterized in that it has a dielectric constant of 1.0 S / cm or more. (2) The additive for a lithium ion secondary battery electrode according to (1) above, characterized in that the average particle diameter D50 of the composite oxide is 1 / 2 or less of the thickness of the lithium ion secondary battery electrode. (3) Ionic conductivity at room temperature is 5×10 -4 The additive for a lithium ion secondary battery electrode according to (1) or (2), characterized in that it has a dielectric constant of 0.05 S / cm or more. (4) The additive for a lithium ion secondary battery electrode according to any one of (1) to (3), characterized in that the element A has d electrons and is in a cationic state with an octahedral coordination selectivity of 50 kJ / mol or more in stabilization by the ligand field of an oxygen anion, and the molar ratio A / La of the element A to La is 0.01 or more and 0.50 or less. (5) The additive for a lithium ion secondary battery electrode according to any one of (1) to (4) above, further comprising an element B which replaces a part of the element La in the crystal structure. (6) The additive for a lithium ion secondary battery electrode according to any one of (1) to (5), wherein the element A is in a cationic state having an octahedral coordination selectivity of 60 kJ / mol or more in stabilization by the ligand field of an oxygen anion. (7) The additive for a lithium ion secondary battery electrode according to any one of (1) to (6) above, wherein the element A is contained in the form of a divalent cation. (8) The additive for a lithium ion secondary battery electrode according to any one of (1) to (7) above, wherein the lattice constant of the crystal structure is 12.93 Å or more. (9) A lithium ion secondary battery comprising the additive for a lithium ion secondary battery electrode according to any one of (1) to (8). (10) A positive electrode sheet for a lithium ion secondary battery, containing the additive for a lithium ion secondary battery electrode according to any one of (1) to (8) in a dispersed form. (11) A lithium ion secondary battery using the positive electrode sheet according to (10). Effect of the Invention

[0013] According to the present invention, it is possible to provide an additive for a lithium ion secondary battery electrode, which reduces the interfacial reaction resistance between the lithium ion secondary battery electrode and the electrolyte solution and reduces the voltage drop, thereby enabling the production of a lithium secondary battery electrode that has particularly excellent input / output characteristics during high-speed charging and discharging, that is, has excellent rate characteristics. [Brief description of the drawings]

[0014] [Figure 1] FIG. 2 is a schematic explanatory diagram for illustrating a presumed mechanism of the effect of the lithium ion secondary battery electrode additive of the present invention. [Diagram 2] FIG. 1 is a schematic diagram showing that the interfacial reaction resistance R2 is reduced by the dielectric polarization action of the additive particles of the present invention (shown as LLZ particles in the figure) present at the interface between the active material particles (shown as positive electrode particles in the figure) of the positive electrode of a lithium ion secondary battery and the electrolyte. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0015] The additive material for the lithium ion secondary battery electrode used in this embodiment is a composite oxide having a garnet-type or garnet-type-like crystal structure containing the elements Li, La, Zr, and O, in which a portion of the element Li is substituted with an element A that is different from the elements and can form Li site vacancies, has a Li site vacancy ratio of 40% to 80%, and has an ionic conductivity of 1×10 at room temperature. -5 It is characterized by having a hardness of 1.0 S / cm or more.

[0016] First, the site will be described. A site is a crystallographically equivalent lattice position. If an atom exists at a lattice position, the site is said to be occupied and is called an occupied site, and if no atom exists at the lattice position, it is called a vacant site. For example, there are five occupied sites in LLZ, which are called the Li1 site, Li2 site, La site, Zr site, and O site. In some cases, they are called the tetrahedral 24d site, the distorted octahedral 96h site, the dodecahedral 24c site, the octahedral 16a site, and the 96h site. In an ideal garnet structure, Li2 can be considered to be located at two equivalent positions (96h) slightly offset from the center of the LiO6 hexahedron in the distorted octahedron, or at the center (48g). In addition, it is possible to identify the occupied sites along with the space group of the crystal by using Rietveld analysis of powder diffraction patterns. Furthermore, the statistical ratio of an atom occupying a site is called the site occupancy, or simply the occupancy, and the ratio of vacancies to all lattice points that an atom can occupy is called the vacancy ratio.

[0017] As shown in FIG. 1(a), a voltage drop ΔV occurs due to the internal resistance R of the battery during charging and discharging in a lithium-ion secondary battery. When the current I increases (when high-speed charging and discharging occurs), the voltage drop increases according to Ohm's law. As a result, the discharge voltage and charge / discharge capacity decrease significantly during high-speed charging and discharging. Therefore, in order to improve the high-speed charging and discharging characteristics (rate characteristics), it is necessary to reduce the internal resistance R. In this case, if we focus on the positive electrode in a lithium-ion secondary battery, the internal resistance is the positive electrode internal resistance, the interface reaction resistance, and the electrolyte resistance, as shown in FIG. 1(b). That is, the additive material of the lithium ion secondary battery electrode of the present invention is brought into contact with the active material of the electrode as shown in FIG. + Ion vacancies and Li + Li due to dielectric polarization by ions + The electrostatic adsorption of ions and solvate molecules causes an interface reaction, which reduces the interface reaction resistance. This reduces the rate of decrease in discharge voltage and charge / discharge capacity during high-speed charge / discharge, improving input / output characteristics.

[0018] By substituting the element A, vacancies are generated at the Li site due to the difference in charge between element A and Li, and the Li site vacancies in the crystal structure increase, so that the dielectric polarization is increased and the interface reaction resistance can be reduced, but if the amount of Li site vacancies (vacancy rate) is too high, the Li content decreases and the conductive carrier ions become too few, resulting in a decrease in electrical conductivity, so that if the amount of Li site vacancies increases beyond a certain level, the ion conductivity decreases. Therefore, the amount of Li site vacancies is preferably 40% or more and 80% or less, more preferably 50% or more and 80% or less, and even more preferably 53% or more and 78% or less. Since Li ions are inserted and removed between the electrode and the electrolyte via the additive material of the lithium ion secondary battery electrode, the mobility of lithium ions during charging and discharging of the lithium ion secondary battery depends on the lithium ion conductivity of the electrolyte, so it is preferable that the lithium ion conductivity of the additive material of the lithium ion secondary battery electrode of the present invention is high. -5 S / cm or more, more preferably 5×10 -4 S / cm or more, and more preferably 1×10 -3 S / cm or more. Good lithium ion mobility can be used to design high-power batteries, but low ionic conductivity means that the solid electrolyte becomes rate-limiting, resulting in poor power characteristics.

[0019] From the above, it is sufficient for the additive material of the lithium ion secondary battery electrode to be in contact with the active material of the electrode, and in order to prevent a decrease in the active material content ratio in the electrode, it is preferable that the particles of the additive material of the lithium ion secondary battery electrode are fine. If the additive material is fine and fine, there will be more contact points with the active material, and the effect of the present invention can be obtained more efficiently. Specifically, it is more preferable that the average particle diameter D50 is 1 / 2 or less of the thickness of the lithium ion secondary battery electrode. Similarly, it is more preferable that the average particle diameter D50 (De) of the additive material of the lithium ion secondary battery electrode is 0.01 or more and 1.0 or less in De / Dc ratio compared with the average particle diameter D50 (Dc) of the positive electrode material (positive electrode active material) of the lithium ion battery. Therefore, the smaller the particle diameter, the better, but a particle diameter of 100 nm or less may be difficult to manufacture or may result in poor yield, making it impractical. Whether the average particle size D50 of the additive in the lithium ion secondary battery electrode is equal to or less than 1 / 2 the thickness of the lithium ion secondary battery electrode can be confirmed, for example, by ultrasonically dispersing the additive using an ultrasonic homogenizer or the like, and then measuring the particle size distribution using a particle size distribution measuring device, thereby confirming the average particle size D50 of the additive (cumulative 50% based on volume).

[0020] The Li ions in the crystalline structure of the additive material of the lithium-ion secondary battery electrode occupy two types of crystallographic sites, Li1 and Li2 sites, which are located in tetrahedral and distorted octahedral sites, respectively. The conduction path of the Li ions in the LLZ is along the Li2→Li1→Li2 sites via the Li1 sites, forming a three-dimensional network of Li ion migration paths within the LLZ structure. Substituting an element into LLZ introduces Li vacancies, stabilizing the cubic crystal and showing high lithium ion conductivity. However, when the substituting element is located at the Li1 site as in Non-Patent Document 2, the free movement of Li along the Li2-Li1-Li2 site is inhibited, which may lead to a decrease in conductivity. Therefore, by including element A in a cationic state with an octahedral coordination selectivity of 50 kJ / mol or more, element A can be selectively substituted for the Li2 site, which is an octahedral site, and the crystal structure can be stabilized by the substitution that stabilizes the coordination.

[0021] This allows the Li charge carrier and Li vacancy ratios to be optimized without impeding the free movement of Li ions along the Li2→Li1→Li2 sites, resulting in high ionic conductivity and stable properties with high dielectric polarization, and further allows the Li vacancy concentration to be increased while ensuring Li ion paths compared to conventional substitution methods. Therefore, increasing the amount of substitution of element A increases the ionic conductivity, but if the amount of substitution is too high, the Li content decreases and the conductive carrier ions become too few, so if the content of element A increases beyond a certain level, the ionic conductivity decreases. A specific example of the element A is preferably Al. 3+ , Ga 3+ , Mg 2+ , Co 2+ , V 3+ , Mn 3+ , Ni 2+ , Cu 2+ Examples of the element include one or two elements selected from the above.

[0022] However, the content of element A is 0.01 or more and 0.50 or less in terms of the molar ratio A / La relative to La. If the content of element A is less than 0.01 in terms of the molar ratio A / La relative to La, sufficient electrical conductivity may not be stably obtained for the reasons described above. On the other hand, if the content of element A is more than 0.50 in terms of the molar ratio A / La relative to La, as explained above, the amount of Li ions serving as conductive carriers may be too small, or the substituted ions may interfere with the Li ion conductive path, resulting in insufficient electrical conductivity. The content of element A is more preferably 0.01 or more and 0.35 or less in terms of the molar ratio A / La relative to La, and even more preferably 0.01 or more and 0.20 or less in terms of the molar ratio A / La relative to La.

[0023] The element A is in a cationic state with a regular octahedral coordination selectivity of 50 kJ / mol or more, that is, the electronic state (particularly the number of d electrons) and valence satisfy the above conditions. 2-When comparing the stabilization by the crystal field (ligand field) of tetrahedral coordination with that of octahedral coordination, it can be determined that the octahedral coordination has a larger stabilization energy and is therefore superior in octahedral selectivity, and in fact it tends to occupy octahedral sites (positions) in oxide crystals. It is known that oxides of typical metal elements (electropositive elements) form ionic crystals (for example, Chemistry Encyclopedia 3, March 10, 1974, condensed edition, 16th printing).

[0024] In this system, when the octahedral coordination selectivity (the difference in coordination stabilization energy between octahedral coordination and tetrahedral coordination) is 50 kJ / mol or more, the ion conductivity is stably increased, and the effect of the present invention is remarkably obtained. This is because, as described above, the element A is effectively substituted at the Li2 site, which is an octahedral site, due to the substitution having octahedral coordination selectivity. Therefore, when the octahedral coordination selectivity is less than 50 kJ / mol, a large ion conductivity cannot be obtained. It is more preferable that the element A contained in the lithium ion conductive oxide material is in a cationic state in which the octahedral coordination selectivity in stabilization by the ligand field of the oxygen anion is 60 kJ / mol or more. When the octahedral coordination selectivity of element A is 60 kJ / mol or more, the element A has a stronger tendency to be fixed at the Li2 site, which is an octahedral site, and the metal ion of element A becomes less mobile due to the stabilization of the coordination, stabilizing the crystal structure. This results in less inhibition of the free movement of Li, and a more stable and higher ionic conductivity.

[0025] The above can be said similarly from the coordination stabilization energy (crystal field stabilization energy CFSE) and the octahedral site preference energy (OSPE). When expressed in terms of the crystal field splitting parameter (10Dq), an OSPE (Δ10Dq) of 2 or more indicates octahedral coordination preference.

[0026] The additive material of the lithium ion secondary battery electrode of the present invention is a composite oxide having a garnet-type or garnet-like crystal structure. The garnet-type crystal structure has a space group of Ia-3d, and the garnet-like crystal structure has a space group of I41 / acd. The basic composition of the composite oxide having a garnet-type crystal structure containing the elements Li, La, Zr, and O is Li7La3Zr2O 12 and the necessary sites for improving the ionic conductivity are substituted.

[0027] When the additive material for the lithium ion secondary battery electrode further contains element B (B is one or more elements selected from Ca, Ba, Sr, Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, and Lu) which replaces a part of the element La, higher ionic conductivity can be obtained and the following effects can be obtained. However, the ionic radius of element B is 0.8 or more relative to La. If an element has an ionic radius of 0.8 or less relative to the ionic radius of La, the ionic conductivity may tend to decrease, so the ionic radius is preferably 0.9 or more, and more preferably 1.0 or more. The effect of the present invention can be easily obtained by adding element B to the additive material of the lithium ion secondary battery electrode, because the decrease in Li ion conductivity is suppressed as much as possible by expanding the crystal lattice of the additive material. If the molar ratio B / La to La greatly exceeds 0.15, the lithium ion conductivity may tend to decrease, and the molar ratio is preferably 0.01 or more and 0.13 or less, and more preferably 0.02 or more and 0.1 or less. From the viewpoint of expanding the crystal lattice, element B is Ba. 2+ or Sr 2+ It is preferable to use Sr 2+ It is more preferable to use

[0028] In the present invention, as described above, the element A contained in the additive material of the lithium ion secondary battery electrode is contained so as to replace a part of the element Li. By replacing a part of the element Li with the element A, the electrode becomes more stable and has a higher ionic conductivity. Whether or not the element A substitutes for a part of the element Li in a garnet-type or garnet-like crystal structure can be confirmed by, for example, performing X-ray diffraction measurement using synchrotron radiation and performing Rietveld analysis using RIETAN-FP based on the obtained X-ray diffraction pattern. It is more preferable that the element A contained in the additive material of the lithium ion secondary battery electrode is contained in the state of a divalent cation. It is considered that the difference in charge between Li and element A creates vacancies at the Li site in the crystal structure, making it easier for Li ions to move (facilitating hopping conduction of Li ions), improving ion conductivity. In other words, this makes it easier to achieve the effects of the present invention. Whether or not element A is contained in the form of a divalent cation can be determined by, for example, using XAFS (X-ray Absorption Fine Structure) to measure the amount of X-ray absorption at an energy near the absorption edge of element A, thereby confirming the valence and coordination number of element A.

[0029] Furthermore, when the additive material for the lithium ion secondary battery electrode further contains an element C (C is one or more elements selected from Sc, Y, Nb, Ta, In, Ge, Sn, and Te) which replaces a part of the element Zr in the crystal structure, a higher ionic conductivity can be obtained and the following effects can be obtained. The effect of the present invention can be easily obtained by adding the element C to the additive material of the lithium ion secondary battery electrode. 4+ It is believed that the difference in charge between element A and element C causes Li ions or Li vacancies to form at the Li sites in the crystal structure, which facilitates the movement of Li ions and improves ionic conductivity. In other words, this makes it easier to achieve the effects of the present invention. The content of element C is preferably 0.01 or more and 0.50 or less in terms of the molar ratio C / La relative to La. If the content of element C is less than 0.01 in terms of the molar ratio C / La relative to La, sufficient electrical conductivity may not be stably obtained for the reasons described above. On the other hand, if the content of element C is more than 0.50 in terms of the molar ratio C / La relative to La, as explained above, the amount of Li ions serving as conductive carriers may be too large or too small, and sufficient electrical conductivity may not be obtained. The content of element C is more preferably 0.01 or more and 0.35 or less in terms of the molar ratio C / La relative to La, and even more preferably 0.01 or more and 0.20 or less in terms of the molar ratio C / La relative to La. From the viewpoint of electrical conductivity, Nb 5+ or Ta 5+ It is more preferable to use

[0030] The additive material for the lithium ion secondary battery electrode is more preferably a crystal structure having a lattice constant of 12.93 Å or more. The higher the lattice constant of a garnet-type or garnet-like crystal structure, the easier it is to achieve high lithium ion conductivity. In other words, this makes it easier to obtain the effects of the present invention. The additive of the lithium ion secondary battery electrode of the present invention may be added together with other additives, and in particular, when added together with zirconium oxide composite oxides containing zirconium oxide, yttrium, scandium, or other rare earth metal ions, the rate characteristics become more excellent.

[0031] The additive material for the lithium ion secondary battery electrode of the present invention may be produced by any production method as long as it satisfies the above-mentioned requirements of the present invention, for example, a gas phase synthesis method such as PVD or CVD, a solid phase reaction method, a spray pyrolysis method, a wet method such as a coprecipitation method or a sol-gel method, etc.

[0032] As an example of a method for producing the additive material for the lithium ion secondary battery electrode of the present invention, a synthesis example by solid-state reaction method can be shown below. As the raw material, sulfates, oxides, carbonates, hydroxides, nitrates, acetates, oxalates, halides, etc. of the constituent elements can be used. For mixing, a planetary mill, a bead mill, a ball mill, or the like can be used. The calcination temperature of the mixture varies depending on the constituent components and the composition (for example, depending on the substituted metal ion), but is preferably 900° C. or higher and 1200° C. or lower. The calcination time varies depending on the constituent components and the composition (for example, depending on the substituted metal ion), but is preferably from 5 hours to 20 hours. The calcination atmosphere is an atmosphere having an appropriate oxygen partial pressure depending on the components and the composition, for example, air, nitrogen, argon, nitrogen or argon with an adjusted oxygen partial pressure, etc. The powder obtained by calcination may be used as it is, or may be further pulverized. For pulverization, a planetary mill, a bead mill, a ball mill, or the like can be used. The particle size after pulverization should be adjusted to an appropriate particle size depending on the application, and usually, D50 is preferably 0.3 μm or more and 20 μm or less.

[0033] As another example of the method for producing the additive material for the lithium ion secondary battery electrode of the present invention, a synthesis example by spray pyrolysis will be shown below. Any raw material may be used as long as it can be dissolved in an aqueous solution or an organic solvent. For example, carbonates, hydroxides, nitrates, acetates, oxalates, halides, metal alkoxides, etc. of the constituent elements can be used. The solvent may be water, an alkane, an alkanecarboxylic acid and / or an alcohol. The temperature of the spray pyrolysis varies depending on the constituent components, the composition, and the solvent concentration (eg, depending on the substituted metal ion), but is usually 200° C. or more and 1200° C. or less. The particle size of the droplets when sprayed is preferably 0.01 μm or more and 100 μm or less. The carrier gas atmosphere is an atmosphere with an appropriate oxygen partial pressure depending on the constituent components and the composition, for example, air, nitrogen, argon, nitrogen or argon with an adjusted oxygen partial pressure, etc. The powder obtained by spray pyrolysis may be used as it is, or may be further pulverized. When pulverizing, a planetary mill, a bead mill, a ball mill, etc. can be used. The particle size after pulverization is preferably adjusted to an appropriate particle size according to the application, but usually, the D50 is preferably 0.3 μm or more and 20 μm or less.

[0034] The lithium-ion secondary battery manufactured using the additive for the lithium-ion secondary battery electrode of the present invention includes a positive electrode having a positive electrode active material that occludes and releases lithium, a negative electrode having a negative electrode active material that occludes and releases lithium, an electrolytic solution that is interposed between the positive electrode and the negative electrode and conducts lithium, a separator provided between the positive electrode and the negative electrode, and the additive for the lithium-ion secondary battery electrode is present in at least one of the positive electrode and the negative electrode. For example, the additive for the lithium-ion secondary battery electrode may be present in the positive electrode or may be present in the negative electrode. By doing so, the interfacial reaction resistance of the electrolytic solution with the positive electrode or the negative electrode is reduced, and the input / output characteristics can be further improved. In the present embodiment, for the sake of convenience of explanation, the case where the additive for the lithium-ion secondary battery electrode is provided in the positive electrode will be mainly described.

[0035] The positive electrode of the lithium-ion secondary battery manufactured using the additive of the present invention is, for example, a mixture of a positive electrode active material, an additive for the lithium-ion secondary battery electrode, a conductive material, and a binder, with an appropriate solvent added to form a paste-like positive electrode material, which is applied and dried on the surface of a current collector, and compressed as necessary to increase the electrode density to form a positive electrode sheet. As the positive electrode active material, sulfides containing transition metal elements, oxides containing lithium and transition metal elements, etc. can be used. Specifically, transition metal sulfides such as TiS2, TiS3, MoS3, FeS2, Li (1-x) MnO2 (0 < x < 1, etc., the same hereinafter), Li (1-x) lithium manganese composite oxides such as Mn2O4, Li (1-x) lithium cobalt composite oxides such as CoO2, Li (1-x)Lithium nickel composite oxides such as NiO2, lithium vanadium composite oxides such as LiV2O3, transition metal oxides such as V2O5, etc. can be used. Among these, lithium transition metal composite oxides, for example, LiCoO2, LiNiO2, LiMnO2, LiV2O3, LiNi 0.80 Co 0.15 Al 0.05 O2, LiNi 0.50 Co 0.20 Mn 0.30 O2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 and the like are preferred.

[0036] The conductive material of the lithium ion secondary battery produced using the additive of the present invention is not particularly limited as long as it is an electronically conductive material that does not adversely affect the battery performance of the positive electrode, and for example, graphite such as natural graphite (scale graphite, flake graphite) and artificial graphite, acetylene black, carbon black, ketjen black, carbon whisker, needle coke, carbon fiber, metals (copper, nickel, aluminum, silver, gold, etc.), or a mixture of two or more of them can be used. Among these, carbon black and acetylene black are preferred as the conductive material from the viewpoints of electronic conductivity and coatability.

[0037] The binder plays a role of binding the active material particles and the conductive material particles, and may be, for example, a fluorine-containing resin such as polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), or fluorine rubber, or a thermoplastic resin such as polypropylene or polyethylene, or an ethylene-propylene-diene mer (EPDM), sulfonated EPDM, or natural butyl rubber (NBR), either alone or as a mixture of two or more of them. In addition, a cellulose-based aqueous binder or an aqueous dispersion of styrene butadiene rubber (SBR) may also be used.

[0038] Examples of solvents that can be used to disperse the positive electrode active material, conductive material, and binder include organic solvents such as N-methylpyrrolidone, dimethylformamide, dimethylacetamide, methyl ethyl ketone, cyclohexanone, methyl acetate, methyl acrylate, diethyltriamine, N,N-dimethylaminopropylamine, ethylene oxide, and tetrahydrofuran.

[0039] Examples of the application method include roller coating such as an applicator roll, screen coating, doctor blade method, spin coating, bar coater, and the like, and any of these can be used to obtain any desired thickness and shape.

[0040] Examples of the current collector include aluminum, titanium, stainless steel, nickel, iron, baked carbon, conductive polymer, conductive glass, and the like, as well as aluminum or copper whose surface has been treated with carbon, nickel, titanium, silver, or the like for the purpose of improving adhesion, conductivity, and oxidation resistance. The surfaces of these can also be subjected to oxidation treatment. The shape of the current collector can be a foil, film, sheet, net, punched or expanded, lath, porous, foamed, or formed of fiber groups. The thickness of the current collector is, for example, 1 to 500 μm.

[0041] The negative electrode of the lithium ion secondary battery produced using the additive of the present invention may be formed, for example, by mixing a negative electrode active material, a conductive material, and a binder, adding an appropriate solvent to form a paste-like negative electrode material, applying it to the surface of a current collector, drying it, and compressing it to increase the electrode density as necessary. Examples of the negative electrode active material include inorganic compounds such as lithium, lithium alloys and tin compounds, carbonaceous materials capable of absorbing and releasing lithium ions, and conductive polymers. The conductive material, binder, solvent, and the like used in the negative electrode may be the same as those exemplified for the positive electrode. The negative electrode current collector can be made of copper, nickel, stainless steel, titanium, aluminum, baked carbon, conductive polymer, conductive glass, Al-Cd alloy, etc., or, for example, copper whose surface has been treated with carbon, nickel, titanium, silver, etc., for the purpose of improving adhesion, conductivity, and reduction resistance. The surface of these can also be oxidized. The shape of the current collector can be the same as that of the positive electrode.

[0042] A non-aqueous electrolyte containing a supporting salt can be used as the electrolyte of the lithium ion secondary battery manufactured using the additive of the present invention. Examples of the solvent of the non-aqueous electrolyte include carbonates, esters, ethers, nitriles, furans, sulfolanes, and dioxolanes, and these can be used alone or in mixture. Specifically, examples of the carbonate include cyclic carbonates such as ethylene carbonate, propylene carbonate, vinylene carbonate, butylene carbonate, and chloroethylene carbonate, chain carbonates such as dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate, ethyl-n-butyl carbonate, methyl-t-butyl carbonate, di-i-propyl carbonate, and t-butyl-i-propyl carbonate, cyclic esters such as γ-butyl lactone and γ-valerolactone, and chain esters such as methyl formate, methyl acetate, ethyl acetate, and methyl butyrate. Among these, a combination of a cyclic carbonate and a chain carbonate is preferred, since this combination not only provides excellent cycle characteristics, which represent the battery characteristics during repeated charging and discharging, but also allows for a well-balanced viscosity of the electrolyte, the electric capacity of the resulting battery, and the battery output.

[0043] Examples of supporting salts contained in the lithium ion secondary battery manufactured using the additive of the present invention include LiPF6, LiClO4, LiAsF6, LiBF4, LiSO3CF3, and LiN(SO3CF3)2. The concentration of this supporting salt in the nonaqueous electrolyte is preferably 0.1 mol / L or more and 5 mol / L or less, and more preferably 0.5 mol / L or more and 2 mol / L or less. When the concentration of the supporting salt is 0.1 mol / L or more, a sufficient current density can be obtained, and when it is 5 mol / L or less, the electrolyte can be more stabilized.

[0044] The lithium ion secondary battery manufactured using the additive of the present invention may have a separator between the negative electrode and the positive electrode. The separator is not particularly limited as long as it has a composition that can withstand the range of use of the lithium secondary battery, and examples thereof include polymer nonwoven fabrics such as polypropylene nonwoven fabrics and polyphenylene sulfide nonwoven fabrics, and thin microporous films of olefin resins such as polyethylene and polypropylene. These may be used alone or in combination.

[0045] The shape of the lithium ion secondary battery produced using the additive of the present invention is not particularly limited, and examples thereof include coin type, button type, sheet type, laminated type, cylindrical type, flat type, square type, etc. In addition, a plurality of such lithium secondary batteries may be connected in series to be applied to large batteries used in electric vehicles, etc.

[0046] As described above, the positive electrode material for lithium ion secondary batteries using the additive for lithium ion secondary battery electrodes of the present invention reduces the interfacial reaction resistance between the positive electrode and the electrolyte, thereby reducing the voltage drop. Therefore, by using the additive of the present invention, a lithium ion secondary battery with high output characteristics can be produced. EXAMPLES

[0047] The present invention will be described below with reference to examples and comparative examples, but the present invention is not limited to the examples.

[0048] (Preparation of additives for lithium-ion secondary battery electrodes) Li2CO3, Al2O3, Ga2O3, MgO, V2O3, Mn2O3, CuO, NiO, La(OH)3, SrCO3, BaO, and ZrO2 were used as raw materials for the additive material of the lithium ion secondary battery electrode. These raw material powders were weighed and mixed to obtain the additive material with the composition shown in Tables 1 to 3. The raw materials were mixed as follows: the weighed raw material powders were put into a poly container together with zirconia balls, and mixed in a ball mill in ethanol for 15 hours, and then dried to obtain a raw material mixture. The charged composition contains more Li2CO3 than the target composition, taking into account the loss of Li during firing. Therefore, even if the charged composition does not satisfy the charge compensation (law of conservation of charge) of the garnet-type crystal structure, it is understood that the composition will satisfy the charge compensation after firing due to the loss of Li and / or oxygen deficiency. In addition, there is substantially no loss of elements other than Li during sintering, and the charged composition ratio is basically maintained even after sintering. The obtained raw material mixture was sintered in an MgO heat-resistant container at 1100°C for 10 hours in air or a nitriding atmosphere. Further, sintering was performed in an MgO heat-resistant container at 1100°C for 4 hours in a nitriding atmosphere to obtain a pre-sintered product. This pre-sintered product was placed in a nylon pot together with zirconia balls, pulverized in ethanol for 2 hours in a planetary ball mill, and then dried to obtain additives No. 1 to 71 (corresponding to the additives of Examples 1 to 67 and Comparative Examples 2 to 5 shown in Tables 1 to 3, respectively) for lithium ion secondary battery electrodes. The particle size of the synthesized powder was measured using additive No. 66 (Example 66) as a representative example, and the average particle size D50 was 1.7 μm.

[0049] Comparative Example 1 The positive electrode active material is a lithium transition metal composite oxide, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3O2 was used. Timcal's product names KS6 and Super-P were used as the conductive additives, and Kureha's product name KF polymer (a solution of PVdF dissolved in N-methylpyrrolidone) was used as the binder. The positive electrode active material: KS6: Super-P: binder was weighed out in a weight ratio of 94:1:2:3, and NMP was added and kneaded to prepare a positive electrode slurry. The obtained slurry was applied to an aluminum current collector by the doctor blade method, dried, punched into a disk shape with a diameter of 13 mm, and pressed to prepare a positive electrode (without additives).

[0050] (Examples 1 to 67 and Comparative Examples 2 to 5) The positive electrodes were prepared using the additive materials No. 1 to 71 for the lithium ion secondary battery electrodes synthesized by the above method. The positive electrode active material was a lithium transition metal composite oxide, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2 was used. Timcal's product names KS6 and Super-P were used as the conductive assistant, and Kureha's product name KF polymer (a solution in which PVdF was dissolved in N-methylpyrrolidone) was used as the binder. The weight ratio of "positive electrode active material: additive: KS6: Super-P: binder" was weighed out in a ratio of "94:1:1:2:3", and NMP was added and kneaded to prepare a positive electrode slurry. The obtained slurry was applied to an aluminum current collector by the doctor blade method, dried, punched into a disk shape with a diameter of 13 mm, and pressed to prepare a positive electrode (positive electrode sheet). The thickness of the positive electrode sheet was measured using Example 66 as a representative example, and was 90 μm.

[0051] (Coin cell assembly) The positive electrode, negative electrode, electrolyte and separator were, in that order, metallic lithium cut into a disk shape, a 1 mol / l solution of LiPF6 solute in a solvent of ethylene carbonate and diethyl carbonate mixed in a volume ratio of 3:7, and a microporous membrane made of polypropylene, and a coin-type battery CR2032 type (diameter 20 mm, height 3.2 mm) was assembled and the battery evaluation measurements were performed.

[0052] (Rate characteristic evaluation) The coin-type lithium secondary battery thus fabricated was initially activated in a thermostatic chamber at 30°C. Charging was performed at a rate of 0.1C with a constant current and constant voltage CCCV with an upper cutoff voltage of 4.23V. Discharging was performed at a rate of 0.1C with a lower discharge voltage limit of 3.0V. Under these conditions, charging and discharging were repeated three times for initial activation. Next, the coin-type lithium secondary battery after the initial activation was charged at a constant current and constant voltage of 4.23 V, which is a rate of 0.1 C, and an upper cut-off voltage, and discharged at a rate of 3 C, with a lower discharge voltage limit of 3.0 V. The discharge capacity of each of the examples and comparative examples at this time was divided by the discharge capacity of Comparative Example 1 (without additive) to calculate the rate characteristic (%). In other words, Rate characteristic (%) = (discharge capacity of each Example and Comparative Example at discharge rate of 3C and lower limit voltage of 3.0V) ÷ (discharge capacity of Comparative Example 1 (no additive) at discharge rate of 3C and lower limit voltage of 3.0V).

[0053] [Crystal structure analysis] Using an X-ray diffractometer (Rigaku smartlab), X-ray diffraction measurements were performed on the synthesized powders of the additives (No. 1 to 71) for lithium-ion secondary battery electrodes, and X-ray diffraction patterns were obtained. It was confirmed that the obtained X-ray diffraction pattern was almost identical to the X-ray diffraction pattern No. 4422259 (Li7La3Zr2O12, space group: Ia-3d (230)) in the CSD (Cambridge Structural Database). Therefore, it can be determined that the additives (No. 1 to 71) for lithium-ion secondary battery electrodes have a garnet-type crystal structure or a garnet-like crystal structure. In addition, based on the obtained X-ray diffraction patterns, Rietveld analysis was performed using Fujio Izumi's multipurpose pattern fitting system RIETAN-FP to calculate the lattice constants of each sample, and the values ​​shown in Tables 1 to 3 were obtained. Furthermore, synchrotron radiation was used to perform X-ray diffraction measurements, and based on the obtained X-ray diffraction pattern, Rietveld analysis was performed using RIETAN-FP to confirm the substitution of element A at the Li site, and the Li occupancy rate could be obtained by refining the occupancy rate at each atomic site. Since the occupancy rate is the statistical ratio at which an atom occupies a site, the vacancy rate where no atom exists was calculated from this, and the Li site vacancy rate shown in Tables 1 to 3 was obtained. Note that RIETAN-FP was used for the Rietveld analysis, but other calculation software can also be used. In addition, the valence and coordination number of element A can be confirmed by measuring the amount of X-ray absorption at energies near the absorption edge of element A using XAFS (X-ray Absorption Fine Structure). The specific method of Rietveld analysis by Fujio Izumi is shown in the second edition of "Practical Application of Powder X-Ray Analysis" by Fujio Izumi.

[0054] The ionic conductivity of the obtained additive material for lithium ion secondary battery electrodes (No. 1 to 71) was measured by preparing a sintered body. The additive material for lithium ion secondary battery electrodes was added with a binder, put into a die with a diameter of 15 mm, and pressed to a thickness of about 11.5 mm to obtain a compact of the additive material for lithium ion secondary battery electrodes. The compact was covered with a calcined powder having the same composition as the compact, and fired at 1200°C for 4 hours in air or a nitriding atmosphere to obtain a sintered body (No. 1 to 71) of the additive material for lithium ion secondary battery electrodes.

[0055] The upper and lower surfaces of the sintered bodies (Nos. 1 to 71) of the additive material for the lithium ion secondary battery electrodes were polished, and then various evaluations and measurements shown below were carried out.

[0056] Relative Density After measuring the mass of the sintered compacts (No. 1 to 71) of the additive material of the lithium ion secondary battery electrode, the length or diameter of each side of the sintered compacts of the additive material of the lithium ion secondary battery electrode and the thickness were measured at several points using a caliper and a micrometer, and the average value was calculated. Using these measurements, the volume of No. 1 to 71 was calculated, and the apparent density was calculated. In addition, after calculating the theoretical density of each composition, the apparent density was divided by the theoretical density and multiplied by 100 to calculate the relative density, and the values ​​shown in Tables 1 to 3 were obtained.

[0057] [Measurement of lithium ion conductivity] After coating both sides of the sample (the polished sintered body obtained above) by Au sputtering, AC impedance measurement was performed at room temperature using an electrochemical measurement system manufactured by N4L (Newtons4th Ltd) to calculate the lithium ion conductivity. As a result, the lithium ion conductivity of each sample was obtained as shown in Tables 1 to 3.

[0058] [Stability evaluation] The sample (sintered sample) whose lithium ion conductivity was measured above was also heat-treated in air at 720°C for 10 hours, and the ion conductivity was then measured in the same manner as above. The conductivity after heat treatment was divided by the conductivity before heat treatment, and multiplied by 100 to calculate the rate of decrease in conductivity due to heat treatment, which was evaluated as the stability of the crystal structure. As a result, the values ​​shown in Tables 1 to 3 were obtained.

[0059] [Table 1]

[0060] [Table 2]

[0061] [Table 3]

[0062] As shown in Tables 1 to 3, in Examples 1 to 67 and Comparative Examples 2 to 5, the conductivity was 1×10 -5 By adding a lithium-ion secondary battery electrode additive with a capacity of S / cm or higher to the positive electrode, the rate characteristics of both are improved.

[0063] Furthermore, as shown in Tables 1 to 3, in Examples 1 to 67 and Comparative Examples 2 to 5, when the molar ratio of element A to La was within the range of 0.01 or more and 0.50 or less and the octahedral selectivity of element A was 50 kJ / mol or more, the stability was 90% or more, indicating high stability. In addition, in Tables 1 to 3, the numerical values ​​in the A / La column are listed with the second decimal place as the significant figure.

[0064] Furthermore, as shown in Tables 1 to 3, when Mg was substituted, the density was improved in all cases, with the relative density reaching 88% or more, and when Sr was added, the lattice constant was expanded in all cases, resulting in higher ionic conductivity.

[0065] Furthermore, when the octahedral selectivity was 60 kJ / mol or more, the stability was 95% or more in all cases, indicating higher stability.

[0066] The additives in the lithium ion secondary battery electrodes of Examples 1 to 67 have an ionic conductivity of 1×10 -5 S / cm or more, but in the case of Examples 60 to 67 in which Sr is added and the A element is a divalent cation, the conductivity is 1×10 -3 The rate characteristic was 135% or more at 0.2 S / cm or more, and higher ionic conductivity and output characteristics were observed. Therefore, by adding the additives of the lithium ion secondary battery electrodes of Examples 1 to 67 to the electrodes, it is possible to manufacture lithium ion secondary batteries with excellent input / output characteristics in which the discharge voltage and charge / discharge capacity are resistant to drops even when charged and discharged at high speed.

[0067] In this embodiment, the average particle diameter D50 of the additive is 1 / 2 or less of the thickness of the lithium ion secondary battery electrode, but the effect of the present invention was confirmed to some extent even when the average particle diameter D50 of the additive is 3 / 4 of the thickness of the lithium ion secondary battery electrode. However, when the average particle diameter D50 of the additive is 1 / 2 or less of the thickness of the lithium ion secondary battery electrode, a more remarkable effect was obtained. It is considered that when the average particle diameter D50 of the additive is 1 / 2 or less of the thickness of the lithium ion secondary battery electrode, the number of contact points between the additive and the active material increases, and better input / output characteristics are obtained. In addition, when the average particle diameter D50 of the additive exceeds the thickness of the lithium ion secondary battery electrode, the separator may be broken and a short circuit may occur, resulting in a decrease in the assembly yield of the battery.

[0068] Furthermore, when a zirconium oxide composite oxide containing zirconium oxide, yttrium, scandium, or other rare earth metal ions was added in addition to the additives of the examples, the rate characteristics were further improved.

[0069] In this embodiment, the additive of the present invention is added to the electrode at 1% by mass, but the effect of the present invention is also seen with an addition of 0.1% by mass, and a more significant effect is obtained by increasing the amount added. However, when the amount added is increased, the amount of active material decreases, and the battery capacity decreases, so that adding 10% by mass or more may not be practical in some cases.

[0070] Furthermore, in addition to the additives of the examples, the rate characteristics were further improved by adding additives of Ta and Nb as representative examples of element C, each of which has a molar ratio C / La of 0.20 to La.

[0071] In this example, the additive was added to the positive electrode, but the same effect was obtained when it was added to the negative electrode. The effect was even greater when it was added to both electrodes.

Claims

1. An additive material to be added to an electrode of a lithium ion secondary battery using an electrolyte solution, the additive material being made of a composite oxide having a garnet-type or garnet-type-like crystal structure containing the elements Li, La, Zr, and O, the element Li being partially substituted with an element A which is different from the elements Li and capable of forming Li site vacancies, the additive material having a Li site vacancy ratio of 40% or more and 80% or less, and an ionic conductivity at room temperature of 1×10 -5 4. An additive for a lithium ion secondary battery electrode, characterized in that the electrical conductivity is 1.0 S / cm or more.

2. 2. The additive for a lithium ion secondary battery electrode according to claim 1, wherein the average particle diameter D50 of the composite oxide is equal to or less than 1 / 2 of the thickness of the lithium ion secondary battery electrode.

3. Ionic conductivity at room temperature is 5×10 -4 3. The additive for a lithium ion secondary battery electrode according to claim 1, wherein the conductivity is 1.0 S / cm or more.

4. The additive for a lithium ion secondary battery electrode according to any one of claims 1 to 3, characterized in that the element A has d electrons and is in a cationic state with a regular octahedral coordination selectivity of 50 kJ / mol or more in stabilization by the ligand field of an oxygen anion, and a molar ratio A / La of the element A to La is 0.01 or more and 0.50 or less.

5. 5. The additive for a lithium ion secondary battery electrode according to claim 1, further comprising an element B which replaces a part of the element La in the crystal structure.

6. The additive for a lithium ion secondary battery electrode according to any one of claims 1 to 5, characterized in that the element A is in a state of a cation having a regular octahedral coordination selectivity of 60 kJ / mol or more in stabilization by the ligand field of an oxygen anion.

7. 7. The additive for a lithium ion secondary battery electrode according to claim 1, wherein the element A is contained in the form of a divalent cation.

8. 8. The additive for a lithium ion secondary battery electrode according to claim 1, wherein the lattice constant of the crystal structure is 12.93 Å or more.

9. A lithium ion secondary battery using an electrolyte solution containing the additive for the lithium ion secondary battery electrode according to any one of claims 1 to 8.

10. A positive electrode sheet for a lithium ion secondary battery using an electrolyte solution containing the additive for the lithium ion secondary battery electrode according to any one of claims 1 to 8 in a dispersed form.

11. A lithium ion secondary battery using an electrolyte, characterized in that the positive electrode sheet according to claim 10 is used.

Citation Information

Patent Citations

  • Preparation method of LiNiLaZrMO solid electrolyte

    CN110256068A

  • Lithium secondary battery

    JP2011113655A

  • Lithium-ion conductive garnet-type compounds

    JP2014529327A

  • Lithium ion-conductive ceramic material and lithium battery

    JP2016040767A

  • Garnet-type lithium ion conductive oxide

    JP2016171068A